2020
DOI: 10.1037/lat0000145
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative lifetime adversity and depression among a national sample of U.S. Latinx immigrants: Within-group differences in risk and protective factors using data from the HCHS/SOL sociocultural ancillary study.

Abstract: Latinx immigrants are exposed to multiple stressors before, during, and after migration. However, most past research has assumed the effects of these stressors are uniform across Latinx groups despite considerable within-group variation. The purpose of this study was to (a) assess the moderating effects of several risk and protective factors on the association between cumulative lifetime adversity and depression among U.S. Latinx immigrants and (b) examine the extent to which risk and protective processes diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
4
15
0
Order By: Relevance
“…A study using the same dataset as in the current study, found differences in exposure to risk factors as well as differences in participants' responses to the risk factors between four Latinx ethnic groups born outside the continental U.S. (i.e., Mexicans, Puerto Ricans, Cubans, and Dominicans) [36].…”
Section: Latinx Subgroup Differencesmentioning
confidence: 51%
See 4 more Smart Citations
“…A study using the same dataset as in the current study, found differences in exposure to risk factors as well as differences in participants' responses to the risk factors between four Latinx ethnic groups born outside the continental U.S. (i.e., Mexicans, Puerto Ricans, Cubans, and Dominicans) [36].…”
Section: Latinx Subgroup Differencesmentioning
confidence: 51%
“…Authors [36] reported significant differences in marital status, household income level, language preference, age, gender, and years lived in the continental U.S. They also found that certain risk factors were associated with mental health for some Latinx ethnic groups, but not for others.…”
Section: Latinx Subgroup Differencesmentioning
confidence: 98%
See 3 more Smart Citations